2016
DOI: 10.1037/cou0000136
|View full text |Cite
|
Sign up to set email alerts
|

Building a pantheoretical model of dehumanization with transgender men: Integrating objectification and minority stress theories.

Abstract: With a national sample of 304 transgender men, the present study tested a pantheoretical model of dehumanization (Moradi, 2013) with hypotheses derived from objectification theory (Fredrickson & Roberts, 1997), minority stress theory (Meyer, 2003), and prior research regarding men's body image concerns. Specifically, we tested common objectification theory constructs (internalization of sociocultural standards of attractiveness [SSA], body surveillance, body satisfaction) as direct and indirect predictors of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 46 publications
10
66
0
Order By: Relevance
“…Appearance congruence was associated negatively with body surveillance but was not directly associated with body shame. This finding parallels prior work that found appearance congruence was negatively associated with body surveillance (Velez et al, 2016), though the observed correlation in the present study was small. Thus, although fostering and increasing appearance congruence may be associated mildly with decreased body monitoring, it does not appear to be directly linked as a robust negative correlate of body shame, disordered eating, or intention to obtain silicone injections.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Appearance congruence was associated negatively with body surveillance but was not directly associated with body shame. This finding parallels prior work that found appearance congruence was negatively associated with body surveillance (Velez et al, 2016), though the observed correlation in the present study was small. Thus, although fostering and increasing appearance congruence may be associated mildly with decreased body monitoring, it does not appear to be directly linked as a robust negative correlate of body shame, disordered eating, or intention to obtain silicone injections.…”
Section: Discussionsupporting
confidence: 91%
“…To begin, we examined the central tenets of objectification theory, which hold that internalization of cultural standards of attractiveness are linked to body surveillance and body shame, and body surveillance is linked to body shame. Consistent with prior studies using a range of diverse samples (Brewster et al, 2014; Brewster et al, 2019; Kozee & Tylka, 2006; Parent & Moradi, 2011; Velez, Breslow, Brewster, Cox, & Foster, 2016; Wiseman & Moradi, 2010), findings from the present study suggest the same pattern of relations among key objectification theory variables. Thus, internalization of cultural standards of attractiveness appears to affect trans women in ways consistent with prior research using other populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…32 Additional stressors include perceived transgender stigma, 33,34 internalized transphobia, 34,35 gender-related rejection and victimization, 31 nonaffirmation of gender identity, 27,36 and nondisclosure of transgender identity. 34 …”
Section: Minority Stress Modelmentioning
confidence: 99%